2016
DOI: 10.14300/mnnc.2016.11034
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest-related stem cells of oral origins in vitro and used in osteoporotic sheep model for being investigated due to therapeutic effects in alveolar bone regeneration

Abstract: giesenhagen B. 4 , sirak s. V. 1 , sletov a. a. 1 , aybazov m. m. 5 , Tebyakina s. V. 1 , shchetinin e. V. 1 , Vukovic m. a. 6 , Koshel i. V. 1 , sirak a. g. 1 , petrosyan g. g. 1 , adamchik a. a. 7 1 stavropol state medical university, russian federation 2 Witten/herdecke university, Witten, germany 3 university of arad, arad, romania 4 university of frankfurt/m., frankfurt am main, germany 5 all-russia research institute of sheep and goat, stavropol, russian federation 6 praxisteam hasslinghausen, germany 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Discrete populations of stem cells (Figure 6 Associated oral tissues such as epithelium, gingiva (gums) and salivary gland also harbor unique populations of stem cells. Molthera GmbH, together with its international cooperation partners, has contributed significantly to the further development of this field of regenerative dentistry since 2005 [21][22][23][24][25], (Figure 6). Stem cells, also known as "progenitor cells", are defined as clonogenic cells capable of both self-renewal and differentiation into multiple lineages.…”
Section: Sources Of Oral Tissues For Stem Cellsmentioning
confidence: 99%
“…Discrete populations of stem cells (Figure 6 Associated oral tissues such as epithelium, gingiva (gums) and salivary gland also harbor unique populations of stem cells. Molthera GmbH, together with its international cooperation partners, has contributed significantly to the further development of this field of regenerative dentistry since 2005 [21][22][23][24][25], (Figure 6). Stem cells, also known as "progenitor cells", are defined as clonogenic cells capable of both self-renewal and differentiation into multiple lineages.…”
Section: Sources Of Oral Tissues For Stem Cellsmentioning
confidence: 99%
“…Within the limits of the present study, it was concluded that both of used models, the tooth extraction site model and the acute 12mm defect model of osteoporotic sheep have shown efficacy for being used in comparative alveolar bone healing research studies. We will be able to use this model for investigating the effect of stem cell supported treatments in regeneration of segmental mandibular bone defects in osteoporotic sheep using ovine NCSCs from palate [7,8,17].…”
Section: оригинальные исследованияmentioning
confidence: 99%
“…The International Society for Cellular and Gene Therapies (ISCT) and the International Society for Extracellular Vesicles (ISEV) recognize the potential of extracellular vesicles (EVs, including exosomes) from mesenchymal stromal cells (MSCs) and possibly other cell sources as treatments for OA (Grimm & Widera, 2019 ; Haque et al., 2019 ; Mellows et al., 2017 ; Skurikhin et al., 2019 ; Wang et al., 2017 ; Zeuner et al., 2016 ). The focus is shifting toward natural alternatives (Dudics et al., 2018 ; Grimm et al., 2016 ; Wang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%